Remote Sensing of the Tautra Ridge: An Overview of the World’s Shallowest Cold-Water Coral Reefs - Aksel Alstad Mogstad; Håvard Snefjellå Løvås; Øystein Sture; Geir Johnsen; Geir Johnsen; Martin Ludvigsen (Frontiers in Marine Science, 2022)
On the Tautra Ridge – a 39-100 m deep morainic sill located in the middle of the Trondheimsfjord, Norway – some of the world’s shallowest known occurrences of the scleractinian cold-water coral (CWC) Desmophyllum pertusum can be found. The earliest D. pertusum records from the Tautra Ridge date back to the 18th century, and since then, the location has provided easy access to physical coral specimens for numerous scientific studies. In 2013, the ridge was declared a marine protected area by the Norwegian Government due to its unique CWC reefs. However, few attempts have to our knowledge yet been made to characterize the distribution, extent and condition of these reefs extensively. The aim of the current study was therefore to add geospatial context to the Tautra CWC reef complex. In the study, data from multibeam echo sounding, synthetic aperture sonar imaging and underwater hyperspectral imaging are used to assess CWC reef occurrences from multiple perspectives. The study demonstrates how complementary remote sensing techniques can be used to increase knowledge generation during seafloor mapping efforts. Ultimately, predictive modeling based on seafloor geomorphometry is used to estimate both distribution and areal coverage of D. pertusum reefs along the majority of the Tautra Ridge. Our findings suggest that D. pertusum reef distribution on the Tautra Ridge is affected by several geomorphometric seafloor properties, and that the total reef extent in the area likely is close to 0.64 km2. Better description of current patterns across the Tautra Ridge will improve our understanding of the interaction between hydrography and geomorphology at the Tautra CWC reef complex in the future.